(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Niche tourism offers an alternative to modern mass tourism. While mass tourism is homogeneous (a standardized, uniform offering for a vast market segment), niche tourism is defined by its heterogeneity (a greater demand for a more distinctive and unique product). It might be argued that niche tourism is developing significantly as a result of a shift in traveler motivational factors [1,2,3]. In recent years, tourism motivation has shifted from traditional strict motives to a more personalized strategy that prioritizes adventurous and meaningful experiences, with customers prepared to pay for them.